2017
DOI: 10.1093/mnras/stx1234
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical tides in exoplanetary systems containing hot Jupiters: confronting theory and observations

Abstract: We study the effect of dynamical tides associated with the excitation of gravity waves in an interior radiative region of the central star on orbital evolution in observed systems containing Hot Jupiters. We consider WASP-43, Ogle-tr-113, WASP-12, and WASP-18 which contain stars on the main sequence (MS). For these systems there are observational estimates regarding the rate of change of the orbital period. We also investigate Kepler-91 which contains an evolved giant star. We adopt the formalism of Ivanov et … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 44 publications
7
29
0
Order By: Relevance
“…Indeed, for stars with a convective core, Barker & Ogilvie (2010) indicated that dynamical tides in radiative zones may be ineffective, thus dynamical tides in radiative zones are expected to be efficient during the transition phase between the end of the main-sequence and the beginning of the convective Heburning core. This is also supported by the analysis of Chernov et al (2017). Inclusion of dynamical tides in radiative zones may therefore change the bottom part (for distances shorter than about 0.05 au) of the middle and bottom right panels of Fig.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Indeed, for stars with a convective core, Barker & Ogilvie (2010) indicated that dynamical tides in radiative zones may be ineffective, thus dynamical tides in radiative zones are expected to be efficient during the transition phase between the end of the main-sequence and the beginning of the convective Heburning core. This is also supported by the analysis of Chernov et al (2017). Inclusion of dynamical tides in radiative zones may therefore change the bottom part (for distances shorter than about 0.05 au) of the middle and bottom right panels of Fig.…”
Section: Discussionsupporting
confidence: 75%
“…An obvious uncertainty arises from the complexity of modeling the tidal interactions. We did not account for the effects of dynamical tides in radiative regions (Goodman & Dickson 1998;Ogilvie & Lin 2007;Barker & Ogilvie 2010;Chernov et al 2017;Weinberg et al 2017). In some circumstances (see below), including this type of tides may affect the fate of short-period planets with respect to what we obtained here, while in other circumstances, the effects may be small.…”
Section: Discussionmentioning
confidence: 85%
“…Tidally excited waves in the stellar radiation zones (Goodman & Dickson 1998;Ogilvie & Lin 2007;Chernov et al 2017) or the wave breaking mechanism at the stellar center (Barker & Ogilvie 2010) could trigger additional tidal dissipation beyond the processes in the convective envelope considered in this study. Further refinements of this theory could be achieved through the consistent modeling of the radial profile of the stellar density, the latter of which is assumed to be constant (though different) in both the stellar core and the envelope in our model (Ogilvie 2013).…”
Section: Discussionmentioning
confidence: 93%
“…This mechanism is able to provide the required level of dissipation to explain the decaying orbit of WASP-12 b (e.g. Barker 2011;Chernov et al 2017;Weinberg et al 2017;Bailey & Goodman 2019), if we assume that these waves are fully dissipated. However, uncertainties remain regarding the structure of the star (whether or not it has a radiative core), and whether these waves should in fact be fully damped.…”
Section: Discussionmentioning
confidence: 99%